2017
DOI: 10.1093/ons/opw020
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Comparison of the Intraoperative Utility of Indocyanine Green and Fluorescein Videoangiographies in Cerebrovascular Surgery

Abstract: In this quantitative analysis of fluorescence study, ICG-VAG showed greater efficacy than FL-VAG in visualizing relatively thick arteries, such as parent artery and STA. However, FL-VAG has greater efficacy than ICG-VAG in visualizing perforating artery, especially in deep surgical fields with characteristic vessel walls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 15 publications
0
19
0
Order By: Relevance
“…However, the quality of image and analysis progressively declines with every administration [12]. Disadvantage of ICG-VA are the limited visualization restricted to the visible operating field [13], the poor image quality in deep operative fields (for instance in surgery of anterior communicating complex), the inability to observe structures (brain, nerve), other than NIR (near infrared) fluorescence images of vessels: the background is in fact black [14,15]. Finally, fluorescence run cannot be observed in real-time through the operating oculars.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…However, the quality of image and analysis progressively declines with every administration [12]. Disadvantage of ICG-VA are the limited visualization restricted to the visible operating field [13], the poor image quality in deep operative fields (for instance in surgery of anterior communicating complex), the inability to observe structures (brain, nerve), other than NIR (near infrared) fluorescence images of vessels: the background is in fact black [14,15]. Finally, fluorescence run cannot be observed in real-time through the operating oculars.…”
mentioning
confidence: 99%
“…The same microscope can also be equipped with integrated ICG-VA and FLOW-800 modules. Matano et al [15] reported on the central intravenous administration of a 250 mg bolus dose of fluorescein, and Narducci et al [12] on the administration of 500 mg through a peripheral vein. As ICG, sodium fluorescein is easy to administer and inexpensive.…”
mentioning
confidence: 99%
See 3 more Smart Citations